2013
DOI: 10.1109/lawp.2013.2255095
|View full text |Cite
|
Sign up to set email alerts
|

Novel Preprocessing Techniques for Accurate Microwave Imaging of Human Brain

Abstract: Two novel preprocessing techniques are applied to reinforce the detection performance and the image quality in microwave imaging systems designed for brain stroke detection. The image of energy distribution is obtained by applying a delay-and-sum beamforming to the backscattered signals measured using a hemielliptical array of 16 corrugated tapered slot antenna elements surrounding the head. The beamformer forms a spatially filtered combination of time-delayed response of scattering points in the head exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 12 publications
0
100
2
3
Order By: Relevance
“…Only the subspace containing useful information is selected, and artifacts are discarded. Head symmetry [15]: The artifacts are removed by subtracting the backscattered signals at antenna that face each other in the array with respect to the head midline, i.e., the central line that divides the head into left and right hemisphere.…”
Section: Preprocessing Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Only the subspace containing useful information is selected, and artifacts are discarded. Head symmetry [15]: The artifacts are removed by subtracting the backscattered signals at antenna that face each other in the array with respect to the head midline, i.e., the central line that divides the head into left and right hemisphere.…”
Section: Preprocessing Phasementioning
confidence: 99%
“…Moreover, a novel algorithm based on PLSR (partial least square regression) has been proposed and compared with the Wiener filtering. In [15], two novel algorithms for stroke detection have been proposed and their performance assessed. They are based on the symmetry with respect to the head midline that divides the head in left and right hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate image reconstruction method is selected based on the particular application. The most frequently used non-linear inversion methods include; Contrast Source Inversion (CSI), GaussNewton Inversion (GNI), Confocal Delay-and-Sum Algorithm and Born Iterative Method (BIM) [8,17,20,28,31,38].…”
Section: Inverse Problem Solutionmentioning
confidence: 99%
“…In 2013, a wideband microwave system for head imaging, utilizing a semielliptical array of 16 corrugated tapered slot antennas (1-4 GHz) installed on an adjustable platform, was presented by Mohammed, et al [8], and Abbosh [30]. A preprocessing algorithm was applied to extract the target response from the strong background reflections [31]. A post-processing algorithm based on confocal delay-and-sum approach and Fermat's principle was developed to construct a high-resolution image of the phantom.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in microwave brain stroke localization has drawn people's interest because of its low cost and portability [1]. Several research groups have reported microwave imaging systems or devices [2][3][4][5][6]. To validate the effectiveness of microwave imaging methods, a phantom imitating human head in electrical and anatomical aspects is required [6][7][8].…”
Section: Introductionmentioning
confidence: 99%